Censorship : opposing viewpoints - Orr, Lisa, 1966- (Opposing viewpoints series (Unnumbered), 1990)
Presents opposing viewpoints about various aspects of censorship and freedom of speech. Includes critical thinking skill activities and a list of organizations to contact.